Économie végétale à partir des études carpologiques du boulevard Dr Henri-Henrot à Reims/Durocortorum - Véronique Matterne (Gallia)
The excavation of a neighborhood on the southern outskirts of Reims, located along the banks of the Vesle, near the boulevard Dr. Henri-Henrot, yielded a particularly diversified collection of carpological material, rich in imported products, composed of a total of 4,668 remains, belonging to 59 taxa, including 8 types of cereals, 3 legumes, 4 oilseed crops, 20 domestic and 12 wild fruit trees, 6 seasoning/aromatic plants, 5 “vegetables”, and 1 species used for dyeing. This carpological study covers a chronological sequence spanning the first years of our era and the first quarter of the 4th c. It thus offers the opportunity to identify the plant foods in circulation within the city during Roman times, as well as the possible transformations that these new species may have introduced into consumption practices. Thus, at least in part, the Roman culture’s degree of penetration into culinary practices and spaces may be observed. The distribution of the main categories of plants within the boulevard Dr. Henri-Henrot site demonstrates a clear predominance of fruit remains, and a good representation of aromatic species, which are very diverse. The two organic layers, US 1630 and 1727, as well as the gutter level, Ca 545 (Us 1658), collected remains of cereals, legumes, oilseed and aromatic plants in higher proportions than in other contexts, suggesting the accumulation of erratic waste consistent with a domestic dump. Domestic fruit trees occupy only a minor place in these assemblages, perhaps because of their larger size. The layers, US 1604 (Ca 225), 1608 (Ca 531), and 1609 (Ca 256), located closer to the river, provide a carpological spectrum very similar to those characterizing the streambed. They all contain high proportions of elements from wild and domestic fruit trees, with a confirmed and solid representation of domestic taxa. A differential selection of remains may have occurred due to the current, the lighter remains having been carried away by the flow, while the heavier ones, such as the Prunus pits, were more easily lodged in the sediment at the edge of the banks. Several exotic species, rarely found in the ancient contexts of northern Gaul, were also reported. Among the culinary herbs, the most remarkable is certainly cumin, originating in Upper Egypt, Iran, Turkey and Turkestan. Discovered in a 1st c. context, the single seed found in Reims constitutes a particularly early example, the other instances in northern France not occurring before the 3rd c. The other spices attested to in Reims or leafy green portions of plants used in cooking to flavor dishes are coriander, savory, dill, celery, and potentially carrot. Black mustard and opium poppy seeds, also considered oilseed plants, may have been used to garnish some food preparations. Among the fruit trees, several species remarkable for their rarity have been identified, notably the almond tree, pomegranate tree, olive tree, and pine tree, but also the peach, medlar and black mulberry, which represent imported products, revealing the importance of urban markets in the provision of exotic species. Almond, olive and pine are represented by a single specimen, while peach pits and pomegranate seeds are much more abundant. The identification of the latter species within the carpological array present on the Reims site contrasts sharply with what is typically known for the plant in northern France, as pomegranate seeds are found in abundance in 28 out of 44 contexts from the boulevard Dr. Henri-Henrot, and this, since the second third of the 1st c. AD. However, no social differentiation by sector is recorded, but rather differences are the reflection of specific activities: food remains stand out from other remains that potentially testify to an artisanal activity centered on the use of reseda luteola. The diversification of fruit trees is recorded especially during the 2nd and early 3rd c., periods during which kitchen utensils were also transformed. The “Romanization” of culinary practices is then no longer merely a façade (Mathelart et al. 2014). The increase in the number of mortars testifies to the importance of spices and the preparation of spiced and carefully seasoned sauces; cooking methods favored for stews or other dishes that are simmered. From the 2nd c. onward, choice of meats is more varied, with the addition of poultry, game, and seafood (Toulemonde et al. 2017). The increased interest in fruits may be part of a profound transformation in table practices; they would find their place within a broader range of uses, as ingredients in sauces, thickeners, in juice, cooked down to make purées, or eaten directly at the table. It is likely that some fruit species were quickly acclimated and produced locally. Alignments of planting pits trace the location of eight orchard complexes around the city of Reims/Durocortorum, six of which were established within 5 km of the ancient city center (Koehler 2003; Achard-Corrompt et al. 2017, p. 521). Different settlement patterns suggest the maintenance of several types of trees or shrubs, but their precise nature could not be determined. These perennial crops required more investment and care than annual crops, but could also be more profitable than cereals, which provided a more limited income. While fruit growing appears to have been well developed, traces of viticulture are more scattered. There are several converging indications around the city of Troyes but none in the direct vicinity of the ancient city of Reims (Zech-Matterne et al. 2011).